Developing teenagers' role consciousness as "world heritage guardians". Issue 2 (15th May 2017) - Wang, Wenhui; Zhang, Yin; Han, Jing; Liang, Ping
Abstract : Purpose: As one of the nearest and most important groups of resource guardians, local teenagers are an important force for current and especially future world heritage protection. Nurturing their awareness of world heritage protection is an important way to achieve the sustainable development of world heritage sites (WHS). The purpose of this paper is to present a case study of local teenagers of Tai'an city in China with the aim of examining how they have developed consciousness of their role as "world heritage guardians." Design/methodology/approach: Semi-structured interviews are used to examine the awareness of 15 local teenagers on world heritage protection. The interview results are then qualitatively analyzed by using a systematic coding process. Findings: The analysis shows that the formation of the guardianship role is realized through three dimensions: recognition, emotion, and action, which are subjected to role awakening, role identifying, and role strengthening stage by stage. The personal experiences of the interviewees, as well as the impact from surrounding groups both serve to influence the formation of their role as "world heritage guardians." Research limitations/implications: The framework constructed in this study on the development of teenagers' role consciousness cannot only apply to world heritage and environmental contexts in terms of awareness of the need for conservation, but be used toward behavioral studies of other age groups. Practical implications: The findings can be used as a practical guide for school teachers, government officials, and heritage managers to better carry out educational programs in terms of heritage tourism and sustainable development of WHS for teenagers. Originality/value: The teenagers' population is underrepresented in the literature in terms of community involvement with world heritage. This study is meaningful because the focus is on improving local teenagers' awareness of the value and importance of world heritage and their preservation.